PERANAN INTERAKSI EDUKATIF DALAM PROSES BELAJAR PESERTA DIDIK MATA PELAJARAN BAHASA INDONESIA KELAS X SMKN 2 BONE - Ranika Salti; Andi Hajar; Asmah Amir (BEGIBUNG: Jurnal Penelitian Multidisiplin, 2024)
This research aims to understand the role of educative interaction in the Indonesian language learning process at SMKN 2 Bone. The research method used in this study is qualitative research. The data obtained and processed are the results of interviews with the Curriculum Vice Principal, Indonesian language teachers, and students of SMKN 2 Bone. Data collection methods used in this research include interviews, observations, and documentation conducted directly at the research site. The results of the research conducted by the author show that educative interaction plays a significant role in the Indonesian language learning process. In the educative interaction during the teaching and learning process, teachers play a crucial role as managers and implementers of the teaching-learning interaction. Teachers act as planners, guides, and motivators to facilitate effective interaction in the learning process. Teachers/educators play a role in creating an environment that keeps students focused on receiving lessons. In this context, teachers/educators behave professionally in performing their duties, making every effort to prevent any disturbances that could affect the students' development and never demeaning the dignity of the students. Through educative interaction, teachers/educators can successfully achieve educational goals.